Correction of Interaction in the Conditions of the Establishment of Digital Economy. - Alekseyenko Lyudmyla Mykhaylivna, Kalashnikov Hennadiy; Алексеєнко Людмила Михайлівна (Львів, Видавництво Львівської політехніки., 2019)
The article raises questions that determine the theoretical and empirical aspects of the scientific study of patterns and contradictions in the development of financial innovations as an economic phenomenon. The methodological basis of the research is the methods of scientific abstraction and synthesis, analysis and synthesis, induction and deduction, methods of theoretical generalization, which made it possible to evaluate the functional vector of financial technologies in the market of financial services.
Keywords: financial technology; digital economy; financial markets; financial assets; financial products